Gender and water insecurity in a subarctic Indigenous community - Hanrahan, Maura; Mercer, Nicholas (The Canadian Geographer / Le Géographe canadien, 2019)
Indigenous communities in Canada suffer disproportionately from compromised water insecurity, with multiple negative implications. Some attention has been paid to gender and water insecurity in developing countries, especially in sub-Saharan Africa, but the topic has been neglected for subarctic settings. We conducted long-term research in Black Tickle, a remote Inuit community in Labrador, Canada, with no piped water and limited access to potable water. Our research was aimed at understanding the multiple dimensions of water security, identifying materialist responses, and conducting a pilot project in domestic rainwater harvesting. Water security emerged as a gendered phenomenon. We supplemented our reflective analysis on this research with two focus group discussions during which Inuit women described their experiences of water security. Participants reported that their physical and mental health are undermined by water insecurity and that water is a source of multiple stresses that demand resilience. Given a developing remittance economy, gender was identified as an increasingly significant determinant of water insecurity in this subarctic community. Having to retrieve water themselves, Inuit women experience altered gender norms and a persistent values conflict in addition to physical strain. Water acquisition is an added responsibility, impacting their labour load. Alternatively, in relying on available men to retrieve water, participants reported feeling guilty and anxious and they worried about men fetching water in dangerous weather conditions and in the vicinity of dangerous wildlife. Participants’ experiences make clear the urgency for a materialist response to water insecurity in the Indigenous subarctic.
Keywords: 2000 à aujourd'hui; accès à l'eau; amériques; canada; communauté Inuit; discipline; environnement; géographie; géographie féministe; labrador; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; thématiques

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge handbooks, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences